Pelatihan Guru Dalam Mendesain Game Edukatif Menggunakan Canva AI: Pengabdian - Riswandi; Muhammad Nurwahidin; Firada Khasbullah; Nursya Fathin Nadiya; Mahdatul Aini Putri; Nayla Alviani Permatasary; Siti Alifah Faiz (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The training program “Designing Educational Games Using Canva AI” was conducted to enhance early childhood teachers’ competencies in utilizing digital technology as a creative and interactive learning medium. This program aimed to strengthen teachers’ understanding of educational game concepts, improve their technical skills in using Canva AI, and encourage the creation of learning media aligned with early childhood developmental characteristics. The training applied an intensive workshop approach consisting of material presentations, demonstrations, hands-on practice, mentoring, and product presentations. Evaluation was carried out through a feedback survey involving 25 participants assessed across ten key indicators. The results showed highly positive responses, particularly in understanding the material, the quality of facilitator guidance, the effectiveness of the workshop method, and increased teacher confidence. Participants successfully produced varied and engaging digital educational games, although challenges remained in enhancing game interactivity and simplifying instructional elements. These findings indicate that the training effectively improved teachers’ digital literacy and creativity, while also highlighting the need for further mentoring to strengthen pedagogical aspects in game design. Overall, the program contributed significantly to preparing early childhood teachers to integrate digital technology into classroom learning.